1996
DOI: 10.1111/j.1365-4362.1996.tb01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Interferon‐alpha 2b in the Treatment of Mature Keloids

Abstract: Only 13 of 22 patients could be evaluated at the end of the study; seven patients withdrew from the study because of severe local pain during injection. Three of the 13 patients showed insignificant reduction in the height of keloids after interferon treatment. No serious laboratory abnormalities were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Recurrence occurred in seven of the 13 in the IFN-α2b group and four of the 26 in the triamcinolone group [13]. al-Khawajah [48] also reported two patients with severe systemic symptoms such as fever, headache, arthralgias, fatigue, chills, and confusion and found that the remainder of the patients experienced some degree of mild flu-like symptoms, which led to the conclusion that this was considered a high-cost therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrence occurred in seven of the 13 in the IFN-α2b group and four of the 26 in the triamcinolone group [13]. al-Khawajah [48] also reported two patients with severe systemic symptoms such as fever, headache, arthralgias, fatigue, chills, and confusion and found that the remainder of the patients experienced some degree of mild flu-like symptoms, which led to the conclusion that this was considered a high-cost therapy.…”
Section: Methodsmentioning
confidence: 99%
“…62 IFN-a2b has also been shown to prohibit hypertrophic scars and keloids through inhibiting cell proliferation and TGF-b1 expression but not by inducing apoptosis, 19 although success with this modality varies, and systemic side effects may occur. 64 Davison and colleagues found IFN-a2b to be less effective than intralesional triamcinolone and terminated their study early because of rapid and frequent recurrences. 63 Al-Khawajah reported two patients with severe constitutional symptoms such as fever, headache, arthralgias, fatigue, chills, and confusion, and remainder of patients experiencing some degree of mild flu-like symptoms, rendering it a failed therapy.…”
Section: Interferon-alpha and -Gammamentioning
confidence: 99%
“…79,80 However, Tredget et al 81 obtained positive results in 7 of 9 patients they treated with hypertrophic scars. Interferon alfa-2b was much less effective at preventing recurrence of keloids after surgical excision in one randomized, controlled study in comparison with intralesional Kenalog.…”
Section: Mastocytosismentioning
confidence: 94%
“…74 Both interferon gamma and interferon alfa-2b have been evaluated as potential monotherapy or adjuvant treatments for keloids and hypertrophic scars (Table VII). 72,[75][76][77][78][79][80][81][82][83] Three small prospective studies involving 23 participants have shown intralesional interferon gamma to be beneficial in the reduction of hypertrophic scar and keloid size. [75][76][77] One small study did not find interferon gamma to be helpful in preventing recurrence of keloids after surgical excision.…”
Section: Mastocytosismentioning
confidence: 98%